Ijtihad Kemanusiaan MDMC dalam Menghadapi Pandemi Covid-19 di Indonesia - Muis, Hasan Sadikin (Humanis; Vol 25 No 4 (2021)DO - 10.24843/JH.2021.v25.i04.p11, 2021)
This study was conducted to determine the sociological impact of MDMC's humanitarian ijtihad in dealing with the Covid-19 pandemic in Indonesia. This research is qualitative by using a phenomenological study of the phenomenon under study, namely by expressing problems, presenting data, analyzing data, and obtaining data through observation either through literature study or directly. The results of this study indicate that MDMC's social care, and solidarity are marked by the establishment of the Muhammadiyah Covid-19 Command Center (MCCC) to fight the Covid-19 pandemic both medically, and outside the medical realm. Muhammadiyah as a religiosity-based community organization takes on a responsible role in responding to the reality of the Covid-19 pandemic with several steps, namely: revitalizing theological rituals, canceling the association's strategic agenda, and engineering learning techniques. These steps are MDMC's humanitarian ijtihad transformed in the face of the Covid-19 pandemic in Indonesia.